DETERMINANTS AFFECTING THE LEVEL OF REGIONAL FINANCIAL INDEPENDENCE - Chairul Adhim; Muh. Syahru Ramadhan; Yeye Suhaety; Mulyati Mulyati; Nurul Hayat; Fahrul Mauzu (International Journal of Social Science, 2023)
This study aims to determine the effectiveness of regional original income, general allocation funds, special allocation funds, and profit-sharing funds that can affect the level of regional financial independence. Sampling using purposive sampling. The research data was tested using multiple linear regression tests with a total sample of 77 local government financial reports. The test uses the SPSS 23 tool. The results of the research on the effectiveness of regional original income do not affect the level of regional financial independence. Meanwhile, general allocation funds, special allocation funds, and profit-sharing funds affect the level of regional financial independence. Then the results of testing the coefficient of determination show that only 36.7% of the dependent variable is able to explain the independent variable. Then the remaining 63.3% is influenced by other variables not used in this study.